KONSEP PENDIDIKAN AKHLAK PADA AL-QUR’AN SURAT LUQMAN AYAT 13-15 - Herwani Herwani (Cross-border, 2020)
This study intends to analyze the concept of morality in the Qur'an Luqman verses 13-15 according to the interpretation of al-Misbah compiled by M. Quraish Shihab. This research uses a qualitative approach and the type of research is Library Research. The data sources are the Qur'an Luqman verses 13-15 and the interpretation of al-Misbah by M. Quraish Shihab which have been compiled in 15 series or volumes since 1999 in Cairo and completed in Jakarta in 2002. The results of this study indicate that there are morals or teachings by Luqman to his children: 1) morals to Allah SWT: a) unite Allah SWT (tawhid), b) grateful, c) repent. 2) morals to fellow human beings: a) respecting parents, b) admonishing ma'ruf nahi munkar, c) patient. 3) morality to the universe. Morals in Islamic civilization are the limiting fence as well as the basis on which the glory of Islam is built. Akhlak is behavior, speech, which comes out spontaneously without requiring a long thought. In Islam, morality is divided into two, namely al-karimah (good) and al-Mazmumah (bad) morals. In order for morals to be good, a process that is taught to children from an early age in the family is needed. The method of inculcating morals in the family includes guidance, habituation and example as taught by Luqman to his children.